Lost in reviews: Looking for the involvement of stakeholders, patients, public and other non‐researcher contributors in realist reviews. (9th October 2020) - Abrams, Ruth; Park, Sophie; Wong, Geoff; Rastogi, Juhi; Boylan, Anne‐Marie; Tierney, Stephanie; Petrova, Mila; Dawson, Shoba; Roberts, Nia
Abstract : The involvement of non‐researcher contributors (eg, stakeholders, patients and the public, decision and policy makers, experts, lay contributors) has taken a variety of forms within evidence syntheses. Realist reviews are a form of evidence synthesis that involves non‐researcher contributors yet this practice has received little attention. In particular, the role of patient and public involvement (PPI) has not been clearly documented. This review of reviews describes the ways in which contributor involvement, including PPI, is documented within healthcare realist reviews published over the last five years. A total of 448 papers published between 2014 and 2019 were screened, yielding 71 full‐text papers included in this review. Statements about contributor involvement were synthesized across each review using framework analysis. Three themes are described in this article including nomenclature, nature of involvement, and reporting impact. Papers indicate that contributor involvement in realist reviews refers to stakeholders, experts, or advisory groups (ie, professionals, clinicians, or academics). Patients and the public are occasionally subsumed into these groups and in doing so, the nature and impact of their involvement become challenging to identify and at times, is lost completely. Our review findings indicate a need for the realist review community to develop guidance to support researchers in their future collaboration with contributors, including patients and the public.